Biplab Kumar Deb: Transformative Leadership in a Federal Context - A Multi-theoretical Analysis of an Emerging Political Visionary - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This comprehensive study examines the leadership trajectory and accomplishments of Biplab Kumar Deb, whose remarkable journey from a refugee background to becoming Chief Minister of Tripura and subsequently a Member of Parliament exemplifies transformative leadership in India's federal system. Through the application of multiple theoretical frameworks, including the revolutionary Transformative Federal Leadership (TFL) framework, this paper analyzes Deb's leadership across seven critical dimensions: transformational capacity, adaptive capacity, policy entrepreneurship, institutional development, collaborative governance, capability expansion, and conflict transformation. The analysis reveals his exceptional ability to orchestrate political change, implement development initiatives, and navigate complex intergovernmental relations while maintaining public trust. His leadership, characterized by vision articulation, grassroots connection, policy innovation, and institutional reform, demonstrates significant potential for expanded national roles. This paper contributes to leadership scholarship by illustrating how integrated theoretical frameworks can provide nuanced insights into political leadership effectiveness within complex federal contexts.